Accessibility of maternal health information and its influence on maternal health preferences in rural Tanzania: A case study of Chamwino District - Hilda A. Mwangakala (AOSIS, 2021)
Background: The access to quality maternal health information amongst pregnant women plays an important role in determining woman’s health behaviour during pregnancy. Yet, access to maternal health information remains a major challenge in Tanzanian rural communities especially for pregnant women leading to low utilisation of skilled maternal health services.